Building a Model for the Risk of water Erosion in Kifri Basin by the Use of Fuzzy Logic - AbdulWahab, Fouad; Jasim, saad (Journal of Tikrit university for humanities - مجلة جامعة تكريت للعلوم الانسانية, 2019)
The study focuses on building a model for water erosion within the semi-mountainous transitional climate characterized by extreme climate elements, tectonic activity and a faulty system of watercourses resulting from an imbalance in the conditions of leadership and border conditions.     These processes reflect an acceleration in the activity of water erosion. Therefore there is a need to identify areas that suffer from the risk of water erosion so as to identify the processes that cause these risks or increase their impact. This  helps  to build an accurate model for estimating the quantities of water erosion. The modern technologies of informational systems and remote sensing data are one of the most successful ways of building models that simulate the reality by providing an appropriate software environment to simulate reality, accuracy in results, and speed of performance and ease of use. Most of the methods that estimate the size of erosion are descriptive equations that do not deal with and model them spatially  by using modern technologies.    The study aimes at using Gavrilovic's EPM model using the logic of the spindle, and then building the Extension in the ARC GIS environment. It contains sub-models that can be used to increase or limit the erosion.